Local and systemic production of nitric oxide in tomato responses to powdery mildew infection - Piterková, Jana; Petrivalský, Marek; Luhová, Lenka; Mieslerová, Barbora; Sedlárová, Michaela; Lebeda, Ales (Molecular plant pathology, 2009)
Various genetic and physiological aspects of resistance of Lycopersicon spp. to Oidium neolycopersici have been reported, but limited information is available on the molecular background of the plant-pathogen interaction. This article reports the changes in nitric oxide (NO) production in three Lycopersicon spp. genotypes which show different levels of resistance to tomato powdery mildew. NO production was determined in plant leaf extracts of L. esculentum cv. Amateur (susceptible), L. chmielewskii (moderately resistant) and L. hirsutum f. glabratum (highly resistant) by the oxyhaemoglobin method during 216 h post-inoculation. A specific, two-phase increase in NO production was observed in the extracts of infected leaves of moderately and highly resistant genotypes. Moreover, transmission of a systemic response throughout the plant was observed as an increase in NO production within tissues of uninoculated leaves. The results suggest that arginine-dependent enzyme activity was probably the main source of NO in tomato tissues, which was inhibited by competitive reversible and irreversible inhibitors of animal NO synthase, but not by a plant nitrate reductase inhibitor. In resistant tomato genotypes, increased NO production was localized in infected tissues by confocal laser scanning microscopy using the fluorescent probe 4-amino-5-methylamino-2',7'-difluorofluorescein diacetate. NO production observed in the extracts from pathogen conidia, together with elevated NO production localized in developing pathogen hyphae, demonstrates a complex role of NO in plant-pathogen interactions. Our results are discussed with regard to a possible role of increased NO production in pathogens during pathogenesis, as well as local and systemic plant defence mechanisms.
Keywords: Plant Diseases; Spores, Fungal; Ascomycota; Plant Leaves; Time Factors; Solanum lycopersicum; Plant Extracts; oxid dusnatý; rostlinné extrakty; listy rostlin; Nitric Oxide; spory hub; časové faktory; nemoci rostlin